Influence of CD8+ T regulatory cells on intraocular tumor development - McKenna, Kyle C.; Previte, Dana M. (Frontiers in Immunology, 2012)
The interior of the eye, or uvea, is a site of immune privilege where certain immune responses are attenuated or completely excluded to protect non regenerating tissues essential for vision. One consequence of this immunoregulation is compromised immune mediated elimination of intraocular tumors. For example, certain murine tumor cell lines which are rejected by host immune responses when transplanted in the skin grow progressively when placed in the anterior chamber (a.c.) of the eye. Progressive ocular tumor growth occurs despite induction of tumor-specific CD8+ T cell responses capable of eliminating a subsequent tumor challenge in the skin or opposite eye. Why these CD8+ T effectors fail to eliminate established ocular tumors is not known. It is well appreciated that growth of tumors in the a.c. induces the generation of immunosuppressive CD8+ T regulatory (Treg) cells. However, the contribution of CD8+ Treg in ocular tumor progression remains unclear. Several studies indicate that these CD8+ Treg target responding CD4+ T cells to inhibit their induction of macrophage-dependent delayed type hypersensitivity (DTH) responses to tumor antigens. However, induction of tumor-specific CD4+ T cell responses does not assure intraocular tumor elimination. This review is focused on how CD8+ Treg could influence the tumoricidal activity of ocular tumor specific CD8+ T effector cells.